Genome-Wide Identification of Long Non-coding RNAs in the Gravid Ectoparasite Varroa destructor - Lin, Zheguang; Liu, Yibing; Chen, Xiaomei; Han, Cong; Wang, Wei; Ke, Yalu; Su, Xiaoling; Li, Yujiao; Chen, Heng; Xu, Hao; Chen, Guohong; Ji, Ting (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) emerge as critical regulators across a wide variety of biological functions in living organisms. However, to date, no systematic characterization of lncRNAs has been investigated in the ectoparasitic mite Varroa destructor, the most severe biotic threat to honey bees worldwide. Here, we performed an initial genome-wide identification of lncRNAs in V. destructor via high-throughput sequencing technology and reported, for the first time, the transcriptomic landscape of lncRNAs in the devastating parasite. By means of a lncRNA identification pipeline, 6,645 novel lncRNA transcripts, encoded by 3,897 gene loci, were identified, including 2,066 sense lncRNAs, 2,772 lincRNAs, and 1,807 lncNATs. Compared with protein-coding mRNAs, V. destructor lncRNAs are shorter in terms of full length, as well as of the ORF length, contain less exons, and express at lower level. GO term and KEGG pathway enrichment analyses of the lncRNA target genes demonstrated that these predicted lncRNAs may be potentially responsible for the regulatory functions of cellular and biological progresses in the reproductive phase of V. destructor. To our knowledge, this is the first catalog of lncRNA profile in the parasitiformes species, providing a valuable resource for genetic and genomic studies. Understanding the characteristics and features of lncRNAs in V. destructor would promote sustainable parasite control.